Deleuze and Guattari’s Rhizome: Racial discrimination in The Bluest Eyes - Salauddin, Nazala (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.